Advantageous Leadership in Public Good Provision: The Case of an Endogenous Contribution Technology - Wolfgang Buchholz; Michael Eichenseer (Center for Economic Studies and ifo Institute (CESifo), 2017)
From the perspective of standard public good theory the total amount of greenhouse gas mitigation (or public good supply in general) will be lower in a leader-follower game than in a simultaneous Nash game so that strategic leadership is disadvantageous for climate policy. We show that this need no longer be true when the leading country has the option to employ a technology by which it can reduce its abatement costs and thus improve the productivity of its contribution technology. Our general result is illustrated by an example with Cobb-Douglas preferences and, finally, an empirical application to global climate policy is briefly discussed.
Keywords: C72; H41; O31; Q54; Q55; 330; public goods; leadership; choice of technology; climate policy